Spatially Resolved Bottom-Side Fluorination of Graphene by Two-Dimensional Substrate Patterning - Bao, Lipiao; Zhao, Baolin; Lloret, Vicent; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
Patterned functionalization can, on the one hand, open the band gap of graphene and, on the other hand, program demanding designs on graphene. The functionalization technique is essential for graphene-based nanoarchitectures. A new and highly efficient method was applied to obtain patterned functionalization on graphene by mild fluorination with spatially arranged AgF arrays on the structured substrate. Scanning Raman spectroscopy (SRS) and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) were used to characterize the functionalized materials. For the first time, chemical patterning on the bottom side of graphene was realized. The chemical nature of the patterned functionalization was determined to be the ditopic scenario with fluorine atoms occupying the bottom side and moieties, such as oxygen-containing groups or hydrogen atoms, binding on the top side, which provides information about the mechanism of the fluorination process. Our strategy can be conceptually extended to pattern other functionalities by using other reactants. Bottom-side patterned functionalization enables utilization of the top side of a material, thereby opening up the possibilities for applications in graphene-based devices.
CRIS-Team Scopus Importer:2020-03-31
Keywords: ditopic functionalization; fluorination; graphene; substrate patterning